Cross-reactive microbial peptides can modulate HIV-specific CD8+ T cell responses - Pohlmeyer, Christopher W.; Laskey, Sarah B.; Beck, Sarah E.; Xu, Daniel C.; Capoferri, Adam A.; Garliss, Caroline C.; May, Megan E.; Livingston, Alison; Lichmira, Walt; Moore, Richard D.; Leffell, M. Sue; Butler, Nicholas J.; et al. (PloS one, 2018)
Heterologous immunity is an important aspect of the adaptive immune response. We hypothesized that this process could modulate the HIV-1-specific CD8+ T cell response, which has been shown to play an important role in HIV-1 immunity and control. We found that stimulation of peripheral blood mononuclear cells (PBMCs) from HIV-1-positive subjects with microbial peptides that were cross-reactive with immunodominant HIV-1 epitopes resulted in dramatic expansion of HIV-1-specific CD8+ T cells. Interestingly, the TCR repertoire of HIV-1-specific CD8+ T cells generated by ex vivo stimulation of PBMCs using HIV-1 peptide was different from that of cells stimulated with cross-reactive microbial peptides in some HIV-1-positive subjects. Despite these differences, CD8+ T cells stimulated with either HIV-1 or cross-reactive peptides effectively suppressed HIV-1 replication in autologous CD4+ T cells. These data suggest that exposure to cross-reactive microbial antigens can modulate HIV-1-specific immunity.